Avaliação da aprendizagem na escola e a questão das representações sociais - Cipriano Carlos Luckesi (EccoS – Revista Científica)
This paper discusses the presence of the teachers social representations phenomenon in the comprehension and practice of the learning evaluation in school, starting from notions that will be very near to common sense and to eventually and sparse readings about the theme. I start explaining what I understand to be social representations and, afterwards, I articulate this comprehension with the questions related to the learning evaluation.